Evaluating the effectiveness of domestic abuse prevention education: are certain children more or less receptive to the messages conveyed? - Fox, Claire L. (Legal and criminological psychology, 2016)
Purpose. A number of school-based domestic abuse prevention programmes have been developed in the United Kingdom, but evidence as to the effectiveness of such programmes is limited. The aim of the research was to evaluate the effectiveness of one such programme and to see whether the outcomes differ by gender and experiences of domestic abuse. Method. Pupils aged 13–14 years, across seven schools, receiving a 6-week education programme completed a questionnaire to measure their attitudes towards domestic violence at pre-, post-test, and 3-month follow-up, and also responded to questions about experiences of abuse (as victims, perpetrators, and witnesses) and help seeking. Children in another six schools not yet receiving the intervention responded to the same questions at pre- and post-test. In total, 1,203 children took part in the research. Results. Boys and girls who had received the intervention became less accepting of domestic violence and more likely to seek help from pre- to post-test compared with those in the control group; outcomes did not vary by experiences of abuse. There was evidence that the change in attitudes for those in the intervention group was maintained at 3-month follow-up. Conclusions. These findings suggest that such a programme shows great promise, with both boys and girls benefiting from the intervention, and those who have experienced abuse and those who have not (yet) experienced abuse showing a similar degree of attitude change.